2019
DOI: 10.1111/ggi.13773
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of pharmacists' assessment and intervention based on Screening Tool for Older Persons' Appropriate Prescriptions for Japanese compared with Screening Tool for Older Persons' Appropriate Prescriptions for Japanese criteria version 2 in older patients with cardiovascular disease

Abstract: Aim This study aimed to evaluate the efficacy of pharmacists' assessment and intervention using the Screening Tool for Older Persons' Appropriate Prescriptions for Japanese (STOPP‐J) to detect and correct potentially inappropriate medications (PIM) compared with the Screening Tool of Older Persons' Potentially Inappropriate Prescriptions (STOPP) criteria version 2. Methods A prospective observational study was carried out at a medical unit of Cardiovascular Surgery and Cardiovascular Internal Medicine in a Jap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 28 publications
5
22
0
Order By: Relevance
“…Furthermore, our study demonstrated that there is also a significant association between PP and PIM use, which is supported by previous reports [8,[20][21][22][23][24][25][26][27]. The frequency of elderly PIM(+) patients in Japan varies from 22.9% to 67.3% [8,22,23,27,31,35,68,71,72] because of different study populations and settings, different definitions of PIMs, or different timings of the investigation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, our study demonstrated that there is also a significant association between PP and PIM use, which is supported by previous reports [8,[20][21][22][23][24][25][26][27]. The frequency of elderly PIM(+) patients in Japan varies from 22.9% to 67.3% [8,22,23,27,31,35,68,71,72] because of different study populations and settings, different definitions of PIMs, or different timings of the investigation.…”
Section: Discussionsupporting
confidence: 88%
“…The list of target drugs, target patient populations, and recommendations developed by the JGS, available on the JGS web page for the STOPP-J in Japanese [55], was used for PIM screening [31]. The list used in this study was shown in Table S1.…”
Section: Patient Characteristics and Medication Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The result was slightly lower than previous results. 11,13,35 This discrepancy may be due to different settings. For instance, those with acute coronary syndrome and cardiovascular diseases without coronary lesions were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, potentially inappropriate medications (PIMs) in older cancer patients have become a growing serious clinical problem, especially after Chen et al and Mohamed et al reported that reducing PIMs can reduce adverse events and prevent premature death in older cancer patients (1,2). To reduce PIMs, it has been reported that not only physicians, who prescribe, but also pharmacists, who detect PIMs and recommend to physicians to discontinue or change the prescription, are important (3)(4)(5). Furthermore, many researchers have reported that pharmacists can reduce PIMs for older cancer patients as well, highlighting the role of these professionals in the field of cancer medicine (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%